2019
DOI: 10.1002/slct.201901535
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Transition from Lotus Leaf to Rose Petal using Modified Fly Ash

Abstract: We present a facile and scalable approach to develop lotus leaf as well rose petal like superhydrophobic surfaces using fly ash (an industrial waste obtained from the burning of coal). To achieve this, as‐obtained fly ash powder with wide particle size distribution (FA) was processed through sedimentation technique to obtain fly ash powder with narrower particle size distribution (FAS) and modified with two different concentrations of stearic acid (SA) and treated at two different temperatures – one each below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Such surfaces can be developed by enhancing the wettability of a material. This can be done by combining roughness with chemical treatment onto the surface [ 84 ]. A surface is said to be superhydrophobic when it exhibits a water contact angle (WCA) above 150°.…”
Section: Antimicrobial Approachesmentioning
confidence: 99%
“…Such surfaces can be developed by enhancing the wettability of a material. This can be done by combining roughness with chemical treatment onto the surface [ 84 ]. A surface is said to be superhydrophobic when it exhibits a water contact angle (WCA) above 150°.…”
Section: Antimicrobial Approachesmentioning
confidence: 99%
“…[169] Copyright 2018, American Institute of Physics. Lotus leaf Superhydrophobicity, self-cleaning, low adhesion [31,32] Mosquito eyes Superhydrophobicity, antifogging [33,34] Salvinia Superhydrophobicity, air-retention [35] Butterfly wings Superhydrophobicity, antireflection, directional adhesion, antifogging [36,37] Shark skin Underwater superoleophobicity, low drag, antifouling [38] Fish scales Underwater superoleophobicity [39,40] Nepenthes pitcher Superhydrophobicity [41][42][43][44][45] Gecko feet Superhydrophobicity, high adhesive, reversible adhesive [46,47] Springtails Superoleophobicity [48][49][50] Rice leaves Directional transport [51,52] Snail shell Superoleophobicity, self-cleaning [53] Rose petals Superhydrophobicity, structural color, high adhesion [54,55] Loquat leaves Anti-corrosion [56] Cicada wing Superhydrophobicity, anti-reflection [57][58][59] Water strider leg Superhydrophobicity, water-repellent, antifogging [60,61] Caterpillar Superhydrophilic; superhydrophobic [62] Nacre Underwater superoleophobicity, mechanical property, strength, [63,64] Adv. Mater.…”
Section: Layout and Shape Of The Microstructuresmentioning
confidence: 99%
“…Bionics have been greatly developed, and artificial superhydrophobic surfaces­(SHS) are constantly synthesized in recent years. The artificial SHS has a significant impact in the fields of anti-icing, , anti-fogging, water collection, , and drag reduction. Among them, the drag reduction of the SHS has achieved great development. The bionic superhydrophobic coating opens up the way for the drag reduction of ships.…”
Section: Introductionmentioning
confidence: 99%
“…Aditya et al 19 used the market hydrophobic coating on the steel ball to do a freefall experiment in Reynolds number of 10 5 −3 × 10. 5 Due to the thin air layer on the surface, the frictional resistance can be reduced by 80%. Wang et al 20 showed the drag-reducing performance is about 16% in the drag sailing experiment using a hull model, which was processed with stearic acid and ethanol.…”
Section: ■ Introductionmentioning
confidence: 99%